1999
DOI: 10.1046/j.1440-1703.1999.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Belowground carbon storage of Micronesian mangrove forests

Abstract: Belowground carbon storage was examined for mangrove forests on Pohnpei Island, Micronesia. Stored carbon in a coral reef‐type mangrove habitat consisting of a 2 m thick mangrove peat layer, which is a type of mangrove habitat in tropical Pacific islands, was estimated at 1300 t C ha−1. The carbon burial rate during the phase of gradual sea‐level rise, which was calculated at 93 g m−2 year−1 between 1800 and 1380 years BP using the medians of the radiocarbon ages, was significantly higher than that betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
53
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 8 publications
9
53
0
2
Order By: Relevance
“…The total amount of C stored in above and below-ground biomass plus sediment was 117.1 ± 16.8 t C ha −1 . These values are within the range observed in other temperate mangrove systems (Howe et al, 2009;Saintilan et al, 2013), yet lower than those values reported from tropical mangrove forests (Table 4; Fujimoto et al, 1999;Alongi et al, 2003;Chmura et al, 2003). Lower C stocks in temperate mangrove forest are predominantly a result of lower mangrove biomass (as described above), as well as lower sediment C stocks.…”
Section: Total Ecosystem Carbon and Nitrogen Stocks In Temperate A Msupporting
confidence: 78%
See 2 more Smart Citations
“…The total amount of C stored in above and below-ground biomass plus sediment was 117.1 ± 16.8 t C ha −1 . These values are within the range observed in other temperate mangrove systems (Howe et al, 2009;Saintilan et al, 2013), yet lower than those values reported from tropical mangrove forests (Table 4; Fujimoto et al, 1999;Alongi et al, 2003;Chmura et al, 2003). Lower C stocks in temperate mangrove forest are predominantly a result of lower mangrove biomass (as described above), as well as lower sediment C stocks.…”
Section: Total Ecosystem Carbon and Nitrogen Stocks In Temperate A Msupporting
confidence: 78%
“…Our total sediment N stocks are also comparable with other tropical mangrove forests (Fujimoto et al, 1999;Ramos e Silva et al, 2007), yet higher than temperate K. obovata sediment in Japan (Khan et al, 2007; Table 4). We speculate that the comparable sediment N stocks yet lower sediment C stocks in our study may be due to a higher proportion of N input originating from external sources (Bouillon et al, 2003), in comparison to peat based organic material (Fujimoto et al, 1999; Chmura et al, 2003;Vegas-Vilarrúbia et al, 2010;Donato et al, 2011).…”
Section: Total Ecosystem Carbon and Nitrogen Stocks In Temperate A Msupporting
confidence: 77%
See 1 more Smart Citation
“…15 Walaupun mangrove diketahui memiliki kemampuan asimilasi dan laju penyerapan C yang tinggi, [16][17][18][19][20][21][22] ternyata data tentang simpanan karbon untuk keseluruhan ekosistem sangat sedikit, yaitu hanya data mengenai emisi C yang terkait dengan konversi lahan. Laporan tentang simpanan C untuk beberapa komponen terutama untuk biomassa pohon juga terbatas 17,18 namun fakta bahwa tanah mangrove yang dalam kaya kandungan organik [22][23][24][25] menunjukkan bahwa dalam estimasi tersebut sejumlah besar karbon keseluruhan ekosistem justru terlewatkan. Tanah mangrove memiliki lapisan suboxic dengan ketebalan berbeda (semula dikenal dengan sebutan 'gambut' atau 'lendut'), yang mendukung berlangsungnya dekomposisi anaerobik dan memiliki kandungan C sedang sampai tinggi.…”
unclassified
“…Tingginya simpanan C per hektar dan distribusinya di seluruh kawasan tropis (luas total 14 juta ha; rujukan 4,6) menunjukkan bahwa mangrove adalah penyimpan C di atas permukaan yang penting secara global. Walaupun contoh-contoh dalam studi kami tidak sepenuhnya mewakili semua jenis mangrove (membuat data ini tidak dapat langsung diberlakukan secara luas), kendala tertentu tentang simpanan C global dapat diperoleh dengan menggabungkan suatu rentang ketidakpastian dari data empiris kami (persentil ke-5 sampai dengan ke-95 dari nilai simpanan C) dengan data global tambahan tentang kandungan C tanah, kedalaman dan biomassa tegakan 16,17,21,23,24 (lihat Metode dalam Informasi Tambahan). Dengan pendekatan ini diperoleh estimasi C sebesar 4-20 Pg secara global.…”
unclassified